2022
DOI: 10.3390/ijerph191610204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese Martial Arts on Motor Skills in Children between 5 and 6 Years of Age: A Randomized Controlled Trial

Abstract: Children’s motor skills can be fully developed only by the appropriate stimulation of physical activities and the environment, and the poor development of motor skills greatly increases the risk of cognitive impairment, obesity, and movement coordination disorder. This study aimed to examine the effects of Chinese martial arts on the motor skills of preschool children aged 5–6 years through a randomized controlled trial. A total of 87 children aged 5–6 years served as participants in a martial arts sensory tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…After reading relevant literature, it was found that the application of various martial arts projects significantly contributes to improving the physical fitness of preschool and school-age children. [2,3] Judo, as a martial art, is beneficial for individuals across different age groups. For example, practicing Judo has a positive impact on movement skills and psychosocial abilities in children with Autism Spectrum Disorder (ASD).…”
Section: Abstract Time Chartmentioning
confidence: 99%
“…After reading relevant literature, it was found that the application of various martial arts projects significantly contributes to improving the physical fitness of preschool and school-age children. [2,3] Judo, as a martial art, is beneficial for individuals across different age groups. For example, practicing Judo has a positive impact on movement skills and psychosocial abilities in children with Autism Spectrum Disorder (ASD).…”
Section: Abstract Time Chartmentioning
confidence: 99%